Large Scale Collections of Biological Material and Ethical First Principles. (April 2014) - Turner, Trudy R.
Abstract Collecting and storing research materials is within the purview of all anthropologists. The establishment of collections, especially the large new biobanks of biological materials, requires an examination of the ways in which ethical first principles of autonomy, beneficence, and justice integrate with the goals and scientific aims of the collection. This article presents an example of the establishment of a repository of material for vervet monkeys (Chlorocebus sensu lato) and the ways in which informed consent, ownership of materials, and data sharing were considered in the establishment of the repository. Concepts of stewardship, derived from museum studies, are provided as an example of the way in which collections are currently regarded and maintained.